Complex coacervation of statistical polyelectrolytes: role of monomer sequences and formation of inhomogeneous coacervates. Issue 10 (28th July 2021) - Yu, Boyuan; Rumyantsev, Artem M.; Jackson, Nicholas E.; Liang, Heyi; Ting, Jeffrey M.; Meng, Siqi; Tirrell, Matthew V.; de Pablo, Juan J.
Abstract : Monomer sequences in statistical (co)polyelectrolytes can be used to tune complex coacervation, including density and structure of the polymer-rich phase. Abstract : Advances in synthetic chemistry have led to greater control over the sequence of polymeric materials, and the ability to create patterns whose complexity is reminiscent of that of biological macromolecules. In random copolymers synthesized via statistical copolymerization, the sequence follows a first-order Markov chain process governed by the underlying reactivity ratios. In this work, theory and simulations are combined to study the role of sequence in the complex coacervation of oppositely charged random (co)polyelectrolytes, i.e. copolymers comprising cationic/anionic and neutral monomers. It is found that charged monomers enhance the proclivity towards complex coacervation, and enhance the coacervates' stability upon addition of salt. This result is general, and holds for both good and poor solvents, despite the different ("closed" and "open") shapes of the respective coacervation binodals. For high charge blockiness, simulations reveal the formation of microphase separated coacervates consisting of domains rich in ionic or neutral monomers. The transition from homogeneous to locally segregated coacervates leads to a non-monotonic dependence of the density on charge blockiness. Our results provide a comprehensive framework to understand and interpret the effects of sequence on complex coacervation, and for rational design of coacervate-based materials.